Pr-AKI: Acute Kidney Injury in Pregnancy – Etiology, Diagnostic Workup, Management - Scurt, Florian G.; Morgenroth, Ronnie; Bose, Katrin; Mertens, Peter R.; Chatzikyrkou, Christos (Geburtshilfe und Frauenheilkunde, 2022)
Despite significant improvements in inpatient and outpatient management, pregnancy-related acute kidney injury (Pr-AKI) remains an important risk factor for early and late maternal and fetal morbidity and mortality. There is a discrepancy between the incidence of Pr-AKI in developing and in developed countries, with the former experiencing a decrease and the latter an increase in Pr-AKI in recent decades. Whereas septic and hemorrhagic complications predominated in the past, nowadays hypertensive disorders and thrombotic microangiopathy are the leading causes of Pr-AKI. Modern lifestyles and the availability and widespread use of in-vitro fertilization techniques in industrialized countries have allowed more women of advanced age to become pregnant. This has led to a rise in the percentage of high-risk pregnancies due to the disorders and comorbidities inherent to or accompanying aging, such as diabetes, arterial hypertension and preexisting chronic kidney disease. Last but not least, the heterogeneity of symptoms, the often overlapping clinical and laboratory characteristics and the pathophysiological changes related to pregnancy make the diagnosis and management of Pr-AKI a difficult and challenging task for the treating physician. In addition to general supportive management strategies such as volume substitution, blood pressure control, prevention of seizures or immediate delivery, each disease entity requires a specific therapy to reduce maternal and fetal complications. In this review, we used the current literature to provide a summary of the physiologic and pathophysiologic changes in renal physiology which occur during pregnancy. In the second part, we present common and rare disorders which lead to Pr-AKI and provide an overview of the available treatment options.
Keywords: pregnancy; acute kidney injury; AKI; Pr-AKI; pathophysiology; cause; diagnosis; management